1995
DOI: 10.1111/j.1600-0722.1995.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some salivary variables between vegetarians and omnivores

Abstract: Johansson G, Ravald N; Comparison of some salivary variables between vegetariatK and omnivores. Eur J Oral Sci 1995; 103; 95-98. © Munksgaard, 1995. The aim of the study was to compare salivary variables in a group of vegetarians with a group of omnivores. Twenty-nine vegetarians, 19 women and 10 men, mean age 35 yr, and 28 omnivores, 20 women and 8 men, mean age 35 yr, were compared in terms of salivary seeretion rate, pH, buffer capacity, mutans streptococci and lactobacilli. The vegetarians had a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
4
1
1
Order By: Relevance
“…On the other hand, "nutritional balance" was not significantly related to the salivary secretion rates. Although one possible explanation is that one or more nutrients may contribute to the salivary secretion rates 2,3) , the present findings do not support this.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…On the other hand, "nutritional balance" was not significantly related to the salivary secretion rates. Although one possible explanation is that one or more nutrients may contribute to the salivary secretion rates 2,3) , the present findings do not support this.…”
Section: Discussioncontrasting
confidence: 57%
“…In previous studies, the saliva samples were collected by mainly chewing paraffin wax 2,3,14) , and in the present study, they were collected using Salivette ® . However, these methods include the possibility that the salivary secretion rates are affected by the individual variation of mastication during the collection of the Lifestyle is defined as "poor" when the HPI score is 0-3, "moderate" when the HPI score is 4-5 and "good" when the HPI score is 6−8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrariamente, a literatura apresenta evidên-cias de que os vegetarianos tenham maior fl uxo salivar 22,23 ou pelo menos que este parâmetro não seja diferente entre vegetarianos e onívoros 24 . Isso está de acordo com outros estudos que verifi caram forte infl uência de dietas ricas em ácidos na secreção de fl uxo salivar antecipatório 25,26 .…”
Section: Resultsunclassified
“…[ 18 ] reported lower flow and pH level of the saliva in vegetarians, which corresponds to our results. However, Johansson and Ravald [ 20 ] observed that the pH level of the saliva was higher among vegetarians than that the control group, although the difference was not statistically significant. They also noticed a remarkable increase in the salivary flow rate in the vegetarian group and considered this the reason for the more alkaline saliva in them.…”
Section: Discussionmentioning
confidence: 99%